2015
DOI: 10.1097/mat.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Double-Lumen Cannula for a Percutaneous RVAD

Abstract: The objectives were to design/fabricate a double lumen cannula (DLC) for a percutaneous RVAD (pRVAD), and to test the feasibility/performance of this pRVAD system. A 27 Fr DLC prototype was made and tested in 6 adult sheep. The pRVAD DLC was inserted into the right jugular vein, advanced through the superior vena cava (SVC)-right atrium (RA)-right ventricle (RV), and ended in the pulmonary artery (PA). A CentriMag pump and optional gas exchanger were connected to the DLC. Blood was withdrawn from RA, pumped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The group of Zwischenberger first described the placement of a single-site, percutaneous, double-lumen cannula for RVAD in an ovine model in 2015. 5 Over the following years, numerous authors have reported cases in which the ProtekDuo has been utilized in multiple configurations including its original configuration as RVAD, RVAD with oxygenator for ECMO (V-P ECMO/OxyRVAD), left ventricular assist device (LVAD), biventricular assist device (BiVAD) or ECPELLA 2.0 when either combined with a durable LVAD or any of the multiple available Impella ® devices. It had also been used as double-lumen drainage cannula for cardiopulmonary bypass (CPB), and in other ECMO configurations, such as veno-pulmonary (V-P), venovenous-pulmonary (VV-P), and in veno-venopulmonary (V-VP) ECMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Zwischenberger first described the placement of a single-site, percutaneous, double-lumen cannula for RVAD in an ovine model in 2015. 5 Over the following years, numerous authors have reported cases in which the ProtekDuo has been utilized in multiple configurations including its original configuration as RVAD, RVAD with oxygenator for ECMO (V-P ECMO/OxyRVAD), left ventricular assist device (LVAD), biventricular assist device (BiVAD) or ECPELLA 2.0 when either combined with a durable LVAD or any of the multiple available Impella ® devices. It had also been used as double-lumen drainage cannula for cardiopulmonary bypass (CPB), and in other ECMO configurations, such as veno-pulmonary (V-P), venovenous-pulmonary (VV-P), and in veno-venopulmonary (V-VP) ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…The group of Zwischenberger first described the placement of a single-site, percutaneous, double-lumen cannula for RVAD in an ovine model in 2015. 5 Over the The ProtekDuo was placed in a late stage after V-V ECMO when either right heart failure or oxygenation problems occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues first described the use of a single-site, dual-lumen cannula for a percutaneous right ventricular assist device (RVAD) with an optional membrane lung (ML) in an ovine model in 2015 [1]. The following year, Aggarwal et al described a patient with combined cardiogenic shock due to right ventricular failure (RVF) and hypoxic respiratory failure, treated with the ProtekDuo® cannula as part of an ECMO system that provided both right ventricle (RV) and respiratory support [2].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral veno-arterial ECMO, by unloading the RV and then, inverting the trans-septal gradient, has been described efficient in situation of high risk pulmonary embolism ( Assouline et al, 2022 ), while same result was suggested using VV ECMO in ARDS ( Miranda et al, 2015 ). Temporary RV assist devices have even been developed, such as double-lumen cannula placed percutaneously ( Wang et al, 2015 ) and advanced through the superior vena cava, the right atrium, the right ventricle and ending in the pulmonary artery. Studies to evaluate these devices are however still needed, but it could be useful in case of severe acute cor pulmonale with high deleterious ventricular interdependence by helping the right ventricle to struggle against an acute rise of pulmonary vascular resistance, situations encountered, for example, in ARDS or in acute chest syndrome due to sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%